Enforced dual‐specificity tyrosine‐regulated kinase 2 expression by adenovirus‐mediated gene transfer inhibits tumor growth and metastasis of colorectal cancer. Issue 3 (10th January 2022) - Imaizumi, Yuta; Yoshida, Saishu; Kanegae, Yumi; Eto, Ken; Yoshida, Kiyotsugu
Abstract: Colorectal cancer is one of the most common gastrointestinal tumors with good outcomes; however, with distant metastasis, the outcomes are poor. Novel treatment methods are urgently needed. Our in vitro studies indicate that dual‐specificity tyrosine‐regulated kinase 2 (DYRK2) functions as a tumor suppressor in colorectal cancer by regulating cell survival, proliferation, and apoptosis induction. In addition, DYRK2 expression is decreased in tumor tissues compared to nontumor tissues in colorectal cancer, indicating a correlation with clinical prognosis. In this context, we devised a novel therapeutic strategy to overexpress DYRK2 in tumors by adenovirus‐mediated gene transfer. The present study shows that overexpression of DYRK2 in colon cancer cell lines by adenovirus inhibits cell proliferation and induces apoptosis in vitro. Furthermore, in mouse subcutaneous xenograft and liver metastasis models, enforced expression of DYRK2 by direct or intravenous injection of adenovirus to the tumor significantly inhibits tumor growth. Taken together, these findings show that adenovirus‐based overexpression of DYRK2 could be a novel gene therapy for liver metastasis of colorectal cancer. Abstract : This is the first report to show that DYRK2 overexpression by intravascularly administered adenoviruses produces an antitumor effect on a mouse model of colorectal cancer liver metastasis. Currently, systemic chemotherapy is the only treatment available for unresectable liver metastases from colorectal cancer. This study could open up a novel therapeutic approach.